Mitochondrial fatty acid β-oxidation is important for normal osteoclast formation in growing female mice - Kushwaha, Priyanka; Alekos, Nathalie S.; Kim, Soohyun P.; Li, Zhu; Wolfgang, Michael J.; Riddle, Ryan C. (Frontiers in Physiology, 2022)
Skeletal remodeling is an energy demanding process that is linked to nutrient availability and the levels of metabolic hormones. While recent studies have examined the metabolic requirements of bone formation by osteoblasts, much less is known about the energetic requirements of bone resorption by osteoclasts. The abundance of mitochondria in mature osteoclasts suggests that the production of an acidified micro-environment conducive to the ionization of hydroxyapatite, secretion of matrix-degrading enzymes, and motility during resorption requires significant energetic capacity. To investigate the contribution of mitochondrial long chain fatty acid -oxidation to osteoclast development, we disrupted the expression of carnitine palmitoyltransferase-2 (Cpt2) in myeloid-lineage cells. Fatty acid oxidation increases dramatically in bone marrow cultures stimulated with RANKL and M-CSF and microCT analysis revealed that the genetic inhibition of long chain fatty acid oxidation in osteoclasts significantly increases trabecular bone volume in female mice secondary to reduced osteoclast numbers. In line with these data, osteoclast precursors isolated from Cpt2 mutants exhibit reduced capacity to form large-multinucleated osteoclasts, which was not rescued by exogenous glucose or pyruvate, and signs of an energetic stress response. Together, our data demonstrate that mitochondrial long chain fatty acid oxidation by the osteoclast is required for normal bone resorption as its inhibition produces an intrinsic defect in osteoclast formation.